Gas hydrate quantification at a pockmark offshore Norway from joint effective medium modelling of resistivity and seismic velocity. (March 2020) - Attias, Eric; Amalokwu, Kelvin; Watts, Millie; Falcon-Suarez, Ismael Himar; North, Laurence; Hu, Gao Wei; Best, Angus I.; Weitemeyer, Karen; Minshull, Tim A.
Abstract: Methane emissions from gas hydrate deposits along continental margins may alter the biogeophysical properties of marine environments, both on local and regional scales. The saturation of a gas hydrate deposit is commonly calculated using the elastic or electrical properties measured remotely or in-situ at the site of interest. Here, we used a combination of controlled-source electromagnetic (CSEM), seismic and sediment core data obtained in the Nyegga region, offshore Norway, in a joint elastic-electrical approach to quantify marine gas hydrates found within the CNE03 pockmark. Multiscale analysis of two sediment cores reveals significant differences between the CNE03 pockmark and a reference site located approximately 150 m northwest of CNE03. Gas hydrates and chemosynthetic bivalves were observed in the CNE03 sediments collected. The seismic velocity and electrical resistivity measured in the CNE03 sediment core are consistent with the P-wave velocity ( V P ) and resistivity values derived from seismic and CSEM remote sensing datasets, respectively. The V P gradually increases ( 1.75–1.9 km/s) with depth within the CNE03 pipe-like structure, whereas the resistivity anomaly remains 3 Ω m. A joint interpretation of the collocated seismic and CSEM data using a joint elastic-electrical effective medium model suggests that for the porosity range 0.55–0.65, the gas hydrate saturation within the CNE03 hydrate stability zone varies with depth between 20 and 48%. At 0.6 porosity, the hydrate saturation within CNE03 varies between 23 and 37%, whereas the weighted mean saturation is 30%. Our results demonstrate that a well-constrained gas hydrate quantification can be accomplished by coupling P-wave velocity and CSEM resistivity data through joint elastic-electrical effective medium modelling. The approach applied in this study can be used as a framework to quantify hydrate in various marine sediments. Highlights: Core data analysis in macro-, meso- and micro-scales provide unequivocal evidence for the existence of gas hydrate at the CNE03 pockmark. Combined elastic-electrical data and effective medium modelling indicate gas hydrate saturation of _ 30% within the CNE03 pipe-like structure. Marine CSEM and seismic data coupled by joint elastic-electrical effective medium modelling yield rigorous and accurate gas hydrate quantification. The modelling concepts and workflow applied can be useful to quantify gas hydrate reservoirs in a pore-filling morphology with fine-grained muddy clay sediment.